Impacts of COVID-19 Pandemic's Distance Learning on Students and Teachers in Schools and in Higher Education: International Perspectives - Harald Burgsteiner; Georg Krammer (Leykam Buchverlagsgesellschaft m.b.H. & Co KG, 2022)
The worldwide imposed lockdowns forced schools and universities to digitise conventional teaching in a very short time and to convert teaching and learning formats partially or completely to Distance Learning. The changes in everyday teaching brought by Distance Learning were felt worldwide. With 22 double blind peerreviewed articles of researchers reporting on 17 different countries, the editors of this book want to shed light on the effects of Distance Learning in different regions of the world. This will allow for a value-free comparison of how the COVID-19 pandemic has been addressed in education in different parts of the world and what impacts it has had, is having or may have in the future.
Keywords: 300; Distance Learning; COVID-19 pandemic; education; universities; schools